Characteristics of Narrative Discourse Processing after Damage to the Right Hemisphere - Marini, Andrea (Seminars in Speech and Language, 2012)
The narrative skills of nonaphasic individuals with right hemisphere damage (RHD) were compared with those of a group of healthy participants. All participants scored within the normal range on tests assessing their level of global cognitive impairment, logical visuospatial reasoning, general linguistic skills, and the potential presence of hemineglect. They were asked to describe the stories portrayed in a set of picture sequences. The individuals with RHD produced descriptions with normal levels of microlinguistic processing but with more tangential errors and conceptually incongruent utterances that lowered their levels of informativeness. A further analysis revealed that these deficits were most evident in persons with anterior lesions to the right hemisphere. These findings lend indirect support to the hypothesis of a major involvement of frontal right hemispheric areas to the process of organization of information in a narrative discourse.
Keywords: Right hemisphere damage; narrative analysis; neurolinguistics; neuropsychology